Analisis Pengaruh Financial Technology terhadap Perkembangan Bisnis Digital dengan Literasi Keuangan sebagai Variabel Mediasi UMKM Kabupaten Jember - Melur Tri Swastika; Mazlina Muhamad; Endang Lifchatullaillah; Raka Elia Nadir; Arum Arya Sukma (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Digital transformation has accelerated the adoption of Financial Technology (FinTech) among Micro, Small, and Medium Enterprises (MSMEs). However, the increasing use of digital financial services has not always been accompanied by optimal digital business development. This study examines the effect of Financial Technology on Digital Business Development, with Financial Literacy as a mediating variable among MSMEs in Sumbersari District, Jember Regency, Indonesia. A quantitative causal approach was employed using data collected from 150 MSME owners through structured questionnaires. Respondents were selected using purposive sampling, and the data were analyzed using Structural Equation Modeling (SEM) with WarpPLS 7.0. The results indicate that Financial Technology does not have a significant direct effect on Digital Business Development. However, Financial Technology has a positive and significant effect on Financial Literacy, while Financial Literacy significantly enhances Digital Business Development. Furthermore, Financial Literacy significantly mediates the relationship between Financial Technology and Digital Business Development, indicating that the benefits of FinTech can be optimized when MSME owners possess adequate financial knowledge and management skills. These findings emphasize the importance of strengthening financial literacy programs to maximize the effectiveness of FinTech adoption and support a more inclusive, competitive, and sustainable digital business ecosystem for MSMEs.